Genre et sexualité dans le rapport pédagogique : ethnographie d’un lycée « de banlieue » - Zoé Rollin (Genre, Sexualité et Société)
Based on fifteen-months of participatory observation and ethnographic research in a suburban high school, this paper aims to analyze the interactions between students and educational staff through the prism of gender and sexuality. In a suburban high school, teenagers' sexuality is totally invisibilised. However, sexuality radiates through all school fields, be it geographical or discursive. The classroom is the place where teenagers' discourses about legitimated forms of sexuality are developed. The pedagogical relationship itself, in its non-instructing dimensions, is highly sexualized.